2019
DOI: 10.1007/s10584-019-02570-y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing risks of apple tree frost damage under climate change

Abstract: Anthropogenic climate change is affecting agriculture and crop production. The responses of horticultural and agricultural systems to changing climatic conditions can be non-linear and at times counter-intuitive. Depending on the characteristics of the system, the actual impact can arise as a result of a combination of climate hazards or compound events. Here, we show that compound events can lead to increased risk of frost damage for apple fruit trees in Germany in a 2°C warmer world of up to 10% relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Among these, temperature and atmospheric CO 2 are the most highlighted climate elements for temperate tree crops. Extensive research in tree phenology has demonstrated that the increase in temperature and atmospheric CO 2 levels ultimately influences the number of chill hours required for dormancy breaking and the yield and fruit quality of temperate fruit crops [10,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] (examples are given in Tables 1 and 2). Several studies have evaluated the productivity of temperate fruit crops with the current status of global climate change [4,33,[44][45][46][47][48][49][50][51][52][53].…”
Section: Climate Change and Temperate Fruit Productivitymentioning
confidence: 99%
“…Among these, temperature and atmospheric CO 2 are the most highlighted climate elements for temperate tree crops. Extensive research in tree phenology has demonstrated that the increase in temperature and atmospheric CO 2 levels ultimately influences the number of chill hours required for dormancy breaking and the yield and fruit quality of temperate fruit crops [10,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] (examples are given in Tables 1 and 2). Several studies have evaluated the productivity of temperate fruit crops with the current status of global climate change [4,33,[44][45][46][47][48][49][50][51][52][53].…”
Section: Climate Change and Temperate Fruit Productivitymentioning
confidence: 99%
“…However, in a warming climate, also the last frost day is occurring earlier in the year and regional studies arrive at contrasting conclusions over the evolution of the frost hazard during flowering. While some studies report on unchanged or increased frequencies [5][6][7][8][9][10][11][12] for certain regions, decreased risks were reported for other regions or by other studies [8][9][10][11][12][13][14][15].…”
Section: Problem Statementmentioning
confidence: 99%
“…In the context of a warming climate, there is agreement that in western and eastern Europe, Australia and South Africa flowering of pome, stone and vine fruit starts earlier [6][7][8][9][10]. However, also the last day of frost in spring occurs earlier [11][12][13][14], resulting in regional studies with contrasting conclusions about the evolution of frost hazard during flowering. Over the past decades, frequency and severity of frosts after bud break decrease in the United States and increase in Europe and Asia [15].…”
Section: Introductionmentioning
confidence: 99%